2014
DOI: 10.1530/rep-14-0222
|View full text |Cite
|
Sign up to set email alerts
|

PARK7 protein translocating into spermatozoa mitochondria in Chinese asthenozoospermia

Abstract: PARK7 (DJ1) is a multifunctional oxidative stress response protein that protects cells against reactive oxygen species (ROS) and mitochondrial damage. PARK7 defects are known to cause various physiological dysfunctions, including infertility. Asthenozoospermia (AS), i.e. low-motile spermatozoa in the ejaculate, is a common cause of human male infertility. In this study, we found that downregulation of PARK7 resulted in increased levels of lipid peroxide and ROS, decreased mitochondrial membrane potential, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Our previous studies confirmed the significant reduction in DJ-1 in the sperm of patients with AS [ 19 , 20 ]. NDUFS3 was identified as a single band of approximately ~30 kDa by Western blot ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our previous studies confirmed the significant reduction in DJ-1 in the sperm of patients with AS [ 19 , 20 ]. NDUFS3 was identified as a single band of approximately ~30 kDa by Western blot ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 90%
“…DJ-1 is expressed after second spermatocytes appear during spermatogenesis and is ultimately mainly located in the sperm head, suggesting an important function for DJ-1 in spermatogenesis [ 17 , 18 ]. Downregulation of DJ-1 was found in ejaculated sperm from Chinese patients with AS, and DJ-1 was shown to translocate into sperm mitochondria during oxidative stress to maintain mitochondrial structure [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Klinefelter, Laskey, Ferrell, Suarez, and Roberts (), for the first time, discovered the relationship between PARK7 and male infertility in Rat (Klinefelter et al, ). The mRNA and protein expression of this gene reduced in AZS men in comparison with normal men (An et al, ), and this decline associated with reactive oxygen species (ROS) increase and damage to mitochondria that lead to sperm motility reduction (Sun et al, ). Sevaral SNPs in the promotor of PARK7 gene have been shown to be associated with asthenozoospermia (Jahantigh, Hosseinzadeh Colagar, & Salimi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the key factor that regulates all these functions will be of prime importance to understand this highly complicated disease pathology. In order to address this issue, we have investigated DJ1, a protein that is abundant in the brain and also a key regulator of DA transmission and reactive oxygen species (ROS) balance ( Blesa and Przedborski, 2014 ; Lopert and Patel, 2014 ; Sun et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…DJ-1 (PARK7) is a neuroprotective protein that protects cells from oxidative stress ( Lopert and Patel, 2014 ; Sun et al, 2014 ). Initially, DJ-1 gene was linked to autosomal recessive early-onset of PD.…”
Section: Introductionmentioning
confidence: 99%